2009
DOI: 10.3928/01913913-20090903-04
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Refraction in a Statistically Significant Sample: Changes According to Age and Strabismus

Abstract: Both the age-related trend in the spherical equivalent and the high hyperopic values of the distribution peak in patients with esodeviation confirm the importance of the hypermetropic refractive component. The statistically significantly higher incidence of astigmatism in patients with 1.00 D or greater ametropia highlights its incidence in amblyopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…10,11,12,13 Low hyperopia is prevalent in the normal population and is not considered pathological. 17 We found only 1 patient with high myopia, which is similar to the frequency observed by other authors. 1 The most frequently observed refractive error in AS was astigmatism.…”
Section: Refractionsupporting
confidence: 92%
“…10,11,12,13 Low hyperopia is prevalent in the normal population and is not considered pathological. 17 We found only 1 patient with high myopia, which is similar to the frequency observed by other authors. 1 The most frequently observed refractive error in AS was astigmatism.…”
Section: Refractionsupporting
confidence: 92%
“…3-5 Many diverse factors, including refractive errors (anisometropia); visual acuity factors (congenital cataracts); genetic factors (congenital fibrosis of extraocular muscle, Marfan's syndrome); brainstem pathology (Duane's syndrome); and muscle pathology (dysthyroid opthalmopathy), likely trigger a cascade of events that result in misaligned eyes. [6][7][8][9][10][11][12][13][14] Despite the generally accepted notion that most strabismus must be a ''brain problem,'' not much is known about how different neural structures contribute to the development and maintenance of the strabismic state. An innervational source for strabismus can be triggered by specific genetic mutations causing structural changes in cranial nerves and thereby resulting in dysinnervation and atrophy of specific extraocular muscles (generally termed as congenital cranial dysinnervation disorders), but these tend to be relatively rare.…”
mentioning
confidence: 99%
“…4,5 Developmental changes in refractive error have also been confirmed by several researchers with reports of decreasing hyperopia or increasing myopia in schoolchildren. [6][7][8][9] Thus, there is a body of research that has demonstrated continuing visual development in acuity and refraction in school-aged children.…”
mentioning
confidence: 99%